1998
DOI: 10.1002/ana.410430618
|View full text |Cite
|
Sign up to set email alerts
|

Codon 219 lys allele of PRNP is not found in sporadic Creutzfeldt‐Jakob disease

Abstract: The polymorphism at codon 219 of the prion protein gene (PRNP) was found in the general Japanese population with 6% allele frequency. Herein, we examined 85 cases of sporadic Creutzfeldt-Jakob disease (CJD) for the codon 219 polymorphism. The codon 219Glu/Lys heterozygous polymorphism was not found in these CJD cases. In addition, we examined 43 patients with dementia of non-CJD origin, and 4 were found to have the codon 219Glu/Lys heterozygous polymorphism with a similar allele frequency as in the general pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
124
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(127 citation statements)
references
References 14 publications
2
124
0
1
Order By: Relevance
“…79,80 First and foremost among these is a polymorphism at PRNP codon 129 between methionine and valine, which has a strong disease susceptibility and phenotype modifying effect. 81 There are marked differences in codon 129 allele frequency worldwide: in the UK and Northern European population, the 129M allele frequency is around 0.65 with a slightly increasing cline through Europe into Africa 79,82 and a marked increasing cline through Asia, 67,83,84 129V is rare in Japan. 129V is the more frequent PRNP allele in only two regions: the Eastern Highlands of Papua New Guinea (PNG) at 0.55, and some Native American populations.…”
Section: Prnp Polymorphisms and Prion Disease Susceptibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…79,80 First and foremost among these is a polymorphism at PRNP codon 129 between methionine and valine, which has a strong disease susceptibility and phenotype modifying effect. 81 There are marked differences in codon 129 allele frequency worldwide: in the UK and Northern European population, the 129M allele frequency is around 0.65 with a slightly increasing cline through Europe into Africa 79,82 and a marked increasing cline through Asia, 67,83,84 129V is rare in Japan. 129V is the more frequent PRNP allele in only two regions: the Eastern Highlands of Papua New Guinea (PNG) at 0.55, and some Native American populations.…”
Section: Prnp Polymorphisms and Prion Disease Susceptibilitymentioning
confidence: 99%
“…A polymorphism at codon 219 between glutamine and lysine (E219K, c.655G4A), found in East Asian populations, also has a profound effect on susceptibility to prion disease. 83 Polymorphisms at codons 142 79 (G142S, c.424G4A) and 171 (N171S, c.512A4G), most frequent in African populations, have not been tested for disease susceptibility effects. A 1-octapeptide repeat deletion (1-OPRD), of which there are differing genetic types with identical protein products, occurs as an uncommon polymorphism in the European population.…”
Section: Prnp Polymorphisms and Prion Disease Susceptibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies of Japanese individuals with the Q219K PrP polymorphism (39) and Suffolk sheep with the Q171R substitution (40,41) suggested that these sequences cannot be converted into PrP Sc . Because Japanese heterozygotes are protected from prion disease, it seemed that PrP(Q219K) exerts a dominant-negative inhibition on prion formation.…”
Section: Biological Significance Of the Structural Similarity Of Dpl mentioning
confidence: 99%
“…A number of point and insert mutations of the PRNP have been linked to familial CreutzfeldtJakob disease (CJD), Gerstmann-Straussler-Scheinker disease (GSS), and fatal familial insomnia (FFI) (McKintosh et al 2003). Morever, polymorphisms of PRNP appear able to influence expression of prion disease in sporadic and iatrogenic CJD Palmer et al 1991;Shibuya et al 1998).…”
Section: Introductionmentioning
confidence: 99%